THE DILEMMA OF THE TRANSFER OF AUTHORITY OF SMA/K FROM REGENCY/CITY TO PROVINCE: STUDY IN BANGKA BELITUNG ISLANDS PROVINCE - Ariska Febriani; Mani Festati Broto; Aos Kuswandi Kuswandi (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The transfer of authority from the district/city government to the provincial government has had major implications in the governance of SMA/K education, as well as what happened in the Bangka Belitung Islands Province. The dilemma as a result of the policy surfaced accompanying the transfer of authority. By using descriptive qualitative method, this study evaluates the policy of the transfer of authority in question. This study found several important things. First, the transfer of authority to manage SMA/K from the district/city government to the provincial government has proceeded well. This is indicated by the transfer of all management authority of SMA/K from the district/city government to the provincial government. Second, there are two main factors in the process of transferring authority, namely supporting factors and inhibiting factors that drive the dynamics in the transfer of authority process. Third, in overcoming the obstacles that arise and taking advantage of the available support, the provincial government has taken several important roles as problem-solving steps. Based on the analysis using the policy evaluation criteria, it is concluded that in terms of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy, the transfer of authority for the management of SMA/K is considered feasible because this policy has substantially encouraged changes for the better, although in each criterion There are some important notes that should be noted.